Estimating abortion prevalence and understanding perspectives of community leaders and providers: Results from a mixed-method study in Istanbul, Turkey. (August 2020) - Huber-Krum, Sarah; Karadon, Duygu; Kurutas, Sebahat; Rohr, Julia; Baykal, Simay Sevval; Okcuoglu, Bahar Ayca; Esmer, Yilmaz; Canning, David; Shah, Iqbal
Objectives: Abortions are difficult to measure; yet, accurate estimates are critical in developing health programs. We implemented and tested the validity of a list experiment of lifetime abortion prevalence in Istanbul, Turkey. We complemented our findings by understanding community perspectives using in-depth interviews with key informants. Methods: We conducted a household survey between March and June 2018. In a random sample of 4040 married women aged 16–44 years, we implemented a double list experiment. We averaged difference in mean values calculations between the average counts for each list to provide an estimated lifetime abortion prevalence. We conducted in-depth interviews with 16 key informants to provide insights into possible explanations for the quantitative results. Results: The abortion prevalence estimate from the list experiment was close to that of the direct question (3.25% vs 2.97%). Key informant narratives suggest that differing definitions of abortion, inaccessibility, provider bias, lack of knowledge of abortion laws and safety, and religious norms could contribute to under-reporting. Results from the qualitative study suggest that abortion is largely inaccessible and highly stigmatized. Conclusion: Measuring experiences of abortion is critical to understanding women's needs and informing harm-reduction strategies; however, in highly stigmatized settings, researchers may face unique challenges in obtaining accurate reports.